2014
DOI: 10.1089/tmj.2012.0328
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Mobile Health Interventions on Chronic Disease Outcomes in Developing Countries: A Systematic Review

Abstract: Introduction: Rates of chronic diseases will continue to rise in developing countries unless effective and cost-effective interventions are implemented. This review aims to discuss the impact of mobile health (m-health) on chronic disease outcomes in low-and middleincome countries (LMIC). Materials and Methods: Systematic literature searches were performed using CENTRAL, MEDLINE, EMBASE, and LILACS databases and gray literature. Scientific literature was searched to identify controlled studies evaluating cell … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
281
0
4

Year Published

2014
2014
2019
2019

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 364 publications
(307 citation statements)
references
References 30 publications
5
281
0
4
Order By: Relevance
“…47-49 A recent systematic review 50 showed that mobile phone-based technology in LMICs positively affects the chronic disease management and their clinical outcomes.…”
Section: New and Promising Strategy For Primary Stroke Preventionmentioning
confidence: 99%
See 1 more Smart Citation
“…47-49 A recent systematic review 50 showed that mobile phone-based technology in LMICs positively affects the chronic disease management and their clinical outcomes.…”
Section: New and Promising Strategy For Primary Stroke Preventionmentioning
confidence: 99%
“…Importantly, easily accessible and cost-effective risk-estimation systems are well suited to the developing world and other regions where access to medical facilities is limited, 37 including elderly populations where smartphones are being increasingly used. [47][48][49] A recent systematic review 50 showed that mobile phone-based technology in LMICs positively affects the chronic disease management and their clinical outcomes.…”
Section: New and Promising Strategy For Primary Stroke Preventionmentioning
confidence: 99%
“…We used the methods described below in all four overviews of health system arrangements and implementation strategies in low-income countries (Ciapponi 2014;Pantoja 2014;Wiysonge 2014).…”
Section: E T H O D Smentioning
confidence: 99%
“…Numerous mHealth technologies were introduced (cf. [10,11]) in an attempt to improve the livelihood of civilians in resource-poor settings whether at a local, regional and/or national level [12,13]. Given the geographic dispersion of healthcare services in developing countries, the interaction of many healthcare providers and the need to balance the complex sequence of events required to care for each patient requires substantial application of mobile technologies [14].…”
Section: Mobile Health (Mhealth) In Developing Countriesmentioning
confidence: 99%